Understanding rig rates - Petter Osmundsen; Knut Einar Rosendahl; Terje Skjerpen (Statistics Norway, Research Department, 2012)
We examine the largest cost component in offshore development projects, drilling rates, which have been high in recent years. To our knowledge, rig rates have not been analysed empirically before in the economic literature. Using econometric analysis, we examine the effects of gas and oil prices, rig capacity utilisation, contract length and lead time, and rig-specific characteristics on Gulf of Mexico rig rates. Having access to a unique data set containing contract information, we are able to estimate how contract parameters crucial to the relative bargaining power between rig owners and oil and gas companies affects rig rates. Our econometric framework is a single equation random effects model, in which the systematic part of the equation is non-linear in the parameters. Such a model belongs to the class of non-linear mixed models, which has been heavily utilised in the biological sciences.
Keywords: C18; C23; L14; L71; Q4; 330; Rig contracts; GoM rig rates; Panel data